HUBUNGAN PEMBERIAN TABLET Fe TERHADAP PRESTASI BELAJAR SISWA/SISWI SMP DI KECAMATAN LINGSAR, LOMBOK BARAT - Nur Atikah; Ajeng Dian Pertiwi; Arief Cahyadin (Pharmaceutical and Traditional Medicine, 2020)
Teenagers are the next generation of Human Resources whose potential needs to be continuously nurtured and developed. The main precondition in this matter that must be fulfilled is Health. Anemia is one of the health problems that occur in adolescents caused by low iron levels in the blood resulting in decreased memory and learning concentration, thus affecting adolescent learning achievement. This study aims to determine the association between compliance of Fe Tablets consumption to the Learning Achievement of Junior High School Students in Lingsar District, West Lombok Regency, by using an observational design and cross-sectional approach. The population of this study was all junior high school students in Lingsar District of West Lombok Regency, and the sample taken was 48 people using a purposive sampling technique. Data analysis using a gamma correlation test with a significance level of 0.05. Data collected was compliance consuming Fe tablets using MMAS-8 questionnaire and learning achievement from report cards. The results showed that there was no significant relationship between the administration of Fe tablets to the learning achievement of junior high school students in Lingsar District, West Lombok Regency with a significant value of 0.791 (p > 0.05).